0.7x-4.6=0.3

Simple and best practice solution for 0.7x-4.6=0.3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.7x-4.6=0.3 equation:


Simplifying
0.7x + -4.6 = 0.3

Reorder the terms:
-4.6 + 0.7x = 0.3

Solving
-4.6 + 0.7x = 0.3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4.6' to each side of the equation.
-4.6 + 4.6 + 0.7x = 0.3 + 4.6

Combine like terms: -4.6 + 4.6 = 0.0
0.0 + 0.7x = 0.3 + 4.6
0.7x = 0.3 + 4.6

Combine like terms: 0.3 + 4.6 = 4.9
0.7x = 4.9

Divide each side by '0.7'.
x = 7

Simplifying
x = 7

See similar equations:

| x/8+4=x/8 | | 2x+5/6=3x+7/6 | | 5-2x=81 | | 58.6*5= | | .50x+.60(20)=.25(102) | | 2x-2=90 | | 1/3x=-9 | | 2-2x=90 | | 2x^2-8x-165=0 | | 12x-5+3x-3=11x-2+3x | | 5(x-7)-2=-37 | | 3x-9+3x-5=12x-3+3x | | 12x^2+13x+1=0 | | 6-(4y-8)=3-5y | | 11x^2-24x-261=0 | | 1/5x-2=-2 | | y=1/5(-5)-2 | | 5-1=0 | | 40x+50y=249 | | -13-2y=-3 | | 2x+3x=400 | | x-2(4)=-3 | | (X-6)/(x+1)=0 | | 67+x=182.50 | | x(x-2)=124 | | (T/t-1)+(2/t+1)=(2/t^2-1) | | 3x+45=10x+24 | | (4x+37)=(3x+43) | | 25=X+7 | | 17=7+27t-16t^2 | | 2x^2-x=2-4x | | b=4a-17-26 |

Equations solver categories